The Gamer Response and Decision Framework: A Tool for Understanding Video Gameplay Experiences. (October 2016) - Gillern, Sam von
Aim . This article presents the Gamer Response and Decision Framework as a tool for understanding how people interpret, make decisions, and learn during their video gaming experiences. Background . The Gamer Response and Decision Framework combines Rosenblatt's Reader Response Theory with a variety of other concepts and frameworks related to new literacies, multimodality, learning theory, psychology, and video gaming. This Framework illustrates that every individual has unique experiences, knowledge, skills, agency, self-efficacy, and goals, and these components influence how people interpret and make decisions during video gameplay, which affects how the game unfolds as a unique experience for each gamer. Together these ideas illustrate that no two gamers have the same experience when playing a video game. Understanding video gameplay experiences is important as it represents a dynamic process in which gamers interpret a wide variety of multimodal symbols, experiment and learn in these digital environments, and solve complex problems in order to progress in the game. Conclusion . The Gamer Response and Decision Framework can be used to understand, investigate, and analyze video gameplay experiences and has significant implications for our understanding the thought, decision-making, and learning processes that gamers experience. In the future, researchers in a variety of fields including education, game studies, and game design can use this framework to analyze how people interact with video games.